2018
DOI: 10.1093/jnci/djy076
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocytes in Patients Receiving Trastuzumab/Pertuzumab-Based Chemotherapy: A TRYPHAENA Substudy

Abstract: Baseline TIL percentage provides independent prognostic information in patients treated with trastuzumab/pertuzumab-based neoadjuvant chemotherapy. However, further validation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 29 publications
(30 reference statements)
3
55
1
Order By: Relevance
“…We analyzed the relationship between TILs and clinicopathological characteristics. As reported in most literature, total TILs are not associated with age or tumor size in breast cancer patients [33,35,39,43,50]. Earlier published showed that there was major correlation between the expression of TILs and lymph node status [49,52], which was similar with our research.…”
Section: Correlation Of Tils With Clinicopathological Parameterssupporting
confidence: 91%
“…We analyzed the relationship between TILs and clinicopathological characteristics. As reported in most literature, total TILs are not associated with age or tumor size in breast cancer patients [33,35,39,43,50]. Earlier published showed that there was major correlation between the expression of TILs and lymph node status [49,52], which was similar with our research.…”
Section: Correlation Of Tils With Clinicopathological Parameterssupporting
confidence: 91%
“…e findings of Kim et al showed that discordance between IHC-based subtypes and PAM50-based intrinsic subtypes was related to inadequate treatment and diminished survival in BC [20]. Studies also indicated that the percentage of stromal tumor-infiltrating lymphocytes (TILs) was associated with a higher pCR rate and improved survival in patients with HER2 + BC [21][22][23]. e optimal predictive biomarkers need further validation to contribute to development of precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…We further explored the ability of CIRI to identify predictive biomarkers in the context of neoadjuvant chemotherapy for locally advanced HER2 + breast adenocarcinoma. We applied our CIRI-BRCA model to publicly available retrospective data from multiple clinical trials where neoadjuvant therapy was given (Esserman et al, 2012;Ignatiadis et al, 2019). We limited our analysis to only patients with HER2 + disease to examine the effect of dual HER2-targeted therapy with trastuzumab and pertuzumab.…”
Section: Comparison Of Ciri To Proportional-hazard Modelingmentioning
confidence: 99%
“…Therefore, we adapted our data-driven approach to deriving priors as used in CIRI to identify parameters related to therapeutic selection. In the case of CLL, this consisted of the therapies used in the CLL8, CLL10, and CLL11 dataset; for breast cancer, this consisted of neoadjuvant chemotherapy ± Trastuzumab as per the ISPY trial (Esserman et al, 2012), or neoadjuvant chemotherapy + Trastuzumab + Pertuzumab as per the TRYPHAENA trial (Ignatiadis et al, 2019). We used our previously established CIRI prognostic model priors for other shared covariates.…”
Section: Prediction Of Therapeutic Benefit In Subsets Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation